Experimental investigation on thermophysical properties of iobiofluids. (January 2022) - Radojčin, Milivoj; Bikić, Siniša; Pavkov, Ivan; Bukurov, Maša; Despotović, Bojana; Stamenković, Zoran; Oluški, Nikola
The aim of this research was to investigate the density, thermal conductivity, and viscosity of dispersions of agricultural biomass particles in ionic liquid [HMIM][NTf2 ] used as a base fluid. This research is a continuation of the development of IoBioFluids, a new class of dispersions obtained by suspending particles produced from agricultural biomass, as a sustainable alternative to IoNanoFluids. Dispersions with different mass concentration of particles (0, 0.5, 1, 2.5, and 5 wt%) were studied at different temperatures (20°C, 30°C, 40°C, and 50°C). Agricultural biomass, namely sunflower stalks, was used for particle production. The dispersion was prepared by applying the commonly used two-step method. In the first step, particles were produced as dry powder from hydrothermal carbonization and heat treatment in the inert atmosphere oven. In the second step, the particles were dispersed into ionic liquid. A rheological investigation showed that dispersions exhibited Newtonian behavior for shear rates over 10 s −1 . Density, thermal conductivity, and dynamic viscosity of dispersions increased with greater mass concentration of particles. Two applied merit criteria suggested a lack of any currently benefit of using the dispersions for heat transfer in the laminar flow regime due to high viscosity of dispersion. The results of criterial analysis showed that experimental data are relatively close to the limit values. Indications are suggesting the possibility of further improvement of IoBioFluid properties as a new heat transfer fluid.